A.The DEVELOPMENT OF MATHEMATICAL LITERACY OF SCHOOLCHILDREN THROUGH DISCOURSES - Abylkassymova, А.Е.; Kappasova, С.Е.; Zhadrayeva, Л.У. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
In our practice, the main goal of pedagogical research is the use of tasks in accordance with the lessons of the "two-way diary" and conceptual learning to develop the reading literacy of students in algebra in the mainstream school through mathematical discourses. Here, the results of the research conducted by students in a group - interpretation of data, analysis with asking questions - based on identification, using the "two-sided diary" approach, a conclusion can be drawn. The subject of algebra in the 7th grade was taken as the objects of study. The research work included the study by students of tasks specially compiled in the group and their analysis by comparing various manifestations of the quantities contained in them, conclusions from the correspondences obtained. In algebra lessons, students develop a conceptual understanding, relying on the laws of natural science for analysis, identification of the relationship between quantities in tasks from real life, i.e., the development of interdisciplinary literacy is carried out.